Los intersticios de la imagen: economías de lo (in)visible e imaginación iconoclasta - Bermúdez Dini, Renato (Eikón / Imago, 2024)
This article proposes the notion of iconoclastic imagination based on images as interstices. In order to do so, firstly, a historical revision of iconoclasm is proposed, not as mere destruction but as a dispute over visuality and power, based on the economy of the (in)visible, according to Marie-José Mondzain. Secondly, from this perspective of political administration based on images, the conceptual category of the interstice in Gilles Deleuze’s philosophy is used to explain iconoclasm as a practice of interweaving and juxtapositions from which new images proliferate. Finally, the notion of iconoclastic imagination is proposed, drawing on the performativity of images articulated by Andrea Soto Calderón, to argue that through it we can articulate other forms of relationship with images and the political powers that inhabit them. This article contributes to the debates on the impact of images from the interdisciplinary crossroads between visual culture studies and the political philosophy of image, and goes beyond the patrimonialist perspective from which art history has studied iconoclasm, to claim it as a practice of critical intervention in our imaginaries.